Clinical, laboratory and radiological profile of dengue among pediatric patients admitted in tertiary care hospital - Jairaj, Sangeetha; D., Sridhar; Reddy, Mettu Pradeep (International Journal Of Community Medicine And Public Health, 2018)
Background: Dengue is found in tropical and subtropical regions around the world, predominantly in urban and semi-urban areas. Dengue mortality can be reduced by implementing early case detection and referral systems for patients; managing severe cases with appropriate treatment; reorienting health services to cope with dengue outbreaks; and training health personnel at all levels of the health system. Many studies that focus on the difference between the frequency of clinical findings in DHF and dengue shock syndrome (DSS) with respect to classical DF has been published. The objectives of the study were to assess signs and symptoms of dengue among patients with severe dengue and patients with dengue fever and to evaluate laboratory and radiological profile among dengue patients. Methods: This Hospital based cross sectional study was conducted on 70 seropositive cases, admitted in the Paediatrics Department of Gandhi hospital during the period of July to December 2017 for 6months. Data was analyzed by using SPPS Version 17 and student t test was used for inferential statistics. Results: Out of 70 cases 38 were presented with severe dengue and 32 presented with dengue fever. Average age of presentation is 7.24 years among severe dengue group, 5.52 years among dengue fever group. In group of severe dengue, 60.5% of the cases were female, which was insignificantly more as compared to 40.6% of the cases from group of dengue fever. Conclusions: All levels of health personnel must be aware of clinical signs and symptoms of all dengue types. Careful monitoring of unusual presentations early recognition severe manifestation and timely intervention can reduce disease specific mortality rate.